Experimental and numerical investigation of tensile behavior of non-laminated CFRP straps. (15th April 2016) - Fan, Haifeng; Vassilopoulos, Anastasios P.; Keller, Thomas
Abstract: Tensile experiments were performed on seven-layer non-laminated carbon fiber-reinforced polymer (CFRP) straps. A corresponding finite element (FE) model was developed and validated by the experimental results. The anchoring of the outermost tape layer by fusion bonding to the adjacent inner layer led to a non-uniform stress distribution among the tape layers on the straight strap segment where the bonding occurred. Stress concentrations at the transition points from the curved to the straight tape segments were negligible compared to the effect of the fusion bonding on the stress level. The strap ultimate load was very sensitive to minor initial damage at the tape edges as well as to stress concentrations in the fusion-bonding area. The latter may lead to a premature failure in the anchoring zone. The innermost tape layer remained fully anchored only by friction up to strap failure.